Classical Islam : a History, 600 A.D. to 1258 A.D. - Von Grunebaum, G. E. (Taylor and Francis, 2017)
"In a book written with the poignancy and beauty appropriate to its subject matter, the author opens by reminding us that the essence of a society is in a sense identical with its history. Classical Islam also serves as a reminder that in the case of Islam, despite its triumphs on the fields of battle, telling its history is the only way open to us to render that essence accessible and show it from all sides. The work offers a grand narrative of a faith that offers an interpretation of the world, a way of life, and a style of thinking, that goes far beyond institutional or political supports. The relevance of this historical perspective is beyond dispute. The period from 610 A.D. when Muhammad received his call until the conquest of Baghdad by the Mongols in 1258 is known as the classical period of Islam. This was the period of the great expansion of Islam both as a political structure and as a religious and intellectual community. It established the base for the development of the high Islamic civilization of North Africa, the Near East, Persia, and India, as well as further expansion of the Islamic religious and intellectual community throughout the world. This book presents an authoritative history of the period written by one of the world's leading experts on the subject. Classical Islam examines the relationships, both cultural and political, between the Islamic world and the Mediterranean countries and India and elaborates on the economic, social, and intellectual factors and forces that shaped the Muslim world and molded its interactions with infidels. The work is written in a clear and direct narrative form, emphasizing simultaneously the major intellectual trends and the political events and tendencies of the formative period in Islamic history that still resonates today."--Provided by publisher